Agresividad y violencia intrafamiliar en niños de la Institución Educativa Inicial N° 62090 Ullpayacu Pastaza Datem del Marañon 2022 - Asipali Napo, Laura (2024)
The purpose of this study was to explore the relationship between aggression and domestic violence in children from I.E.I. N°62090 Ullpayacu Pastaza, in Datem del Marañón, addressing the research question of how these two variables are related in the mentioned context. A total of 120 students were selected as the population and sample for this analysis, using a relational approach and a field, cross-sectional, and bivariate study design. Data collection was carried out through observation techniques and surveys, using an observation guide and a questionnaire as the main tools, which were previously validated by experts on the subject. The findings showed, through a Student's t-test statistic of 8.147 and a p-value of 0.000 (significantly lower than 0.05), that it is possible to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) with a confidence level of 5%. This indicates that there is a statistically significant relationship between aggression and domestic violence in the children studied, thus confirming the hypothesis proposed in the research.